2023
DOI: 10.1002/saj2.20490
|View full text |Cite
|
Sign up to set email alerts
|

Organic carbon controls water retention and plant available water in cultivated soils from South Greenland

Abstract: The warming climate is rapidly changing the circumpolar region, presenting new opportunities and challenges for agricultural production in South Greenland. The warming climate is projected to increase the frequency of drought periods, but little is known about the soil-water retention (SWR) and the plant available water (PAW) of the agricultural soils in the region. This study aimed to measure the SWR and PAW of Greenlandic agricultural soils and evaluate the effect of organic carbon (OC) and clay (CL) content… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
(92 reference statements)
0
3
0
Order By: Relevance
“…From each site, soil cores were prepared for incubation at a standardised matric potential (ψ m ) of −100 hPa (referred to as pF 2) and at the in situ water content. Adjustment to pF 2 by controlled wetting and drying on sandboxes 52 was achieved in 2 weeks and allowed the effects of OC on CO 2 emissions to be studied without the interaction of randomly different soil water status at the sampling times. However, CO 2 emissions were also measured at in situ water contents to substantiate the rate measurements with pF 2 adjustment and to assess the role of OC content in CO 2 emissions at discrete water content classes.…”
Section: Incubations and Measurement Of Co 2 Emissionsmentioning
confidence: 99%
“…From each site, soil cores were prepared for incubation at a standardised matric potential (ψ m ) of −100 hPa (referred to as pF 2) and at the in situ water content. Adjustment to pF 2 by controlled wetting and drying on sandboxes 52 was achieved in 2 weeks and allowed the effects of OC on CO 2 emissions to be studied without the interaction of randomly different soil water status at the sampling times. However, CO 2 emissions were also measured at in situ water contents to substantiate the rate measurements with pF 2 adjustment and to assess the role of OC content in CO 2 emissions at discrete water content classes.…”
Section: Incubations and Measurement Of Co 2 Emissionsmentioning
confidence: 99%
“…The formation of meso-and macro-aggregates is accompanied by an increase in total porosity through a reduction in the proportion of small pore sizes in soil with a high fine particle fraction content (Jensen et al, 2020;. This increased porosity creates pore spaces in soil that can be occupied by water (Weber et al, 2023). Organic carbon stored between and within soil aggregates contributes significantly to increasing water retention capacity at various levels of water potential (Yang et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…One way of improving irrigation efficiency is to enhance the SWR. For that, various studies have shown the influence of organic matter content on increasing this property [4,5]. Panagea et al [6] studied the impact of soil organic carbon (SOC) changes due to different management strategies on the SWR of loamy soils in long-term experiments in Europe.…”
Section: Introductionmentioning
confidence: 99%